KEPUTUSAN PEMILIHAN MASYARAKAT TERHADAP ANGKUTAN UMUM PERKOTAAN BUS TRANS METRO PEKANBARU - Trisna, Meilisa; Tantoro, Swiss (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The transport system is an integral part of any regional infrastructure, both urban and rural areas, the developed countries or developing the transportation planning is closely related to economic and social policy broadly. A tool that is often used public transportation Pekanbaru city is public transportation, city buses and Bus Rapid Transit Trans Metro Pekanbaru or can be shortened to Bus TMP. This research on the public decision choosing public transport Trans Metro bus Pekanbaru as a means of public transport.Research on the selection decisions on Trans Metro bus include time, cost of service users, safety and security, pleasure and comfort of service users. This is seen from the questionnaires distributed. Researchers to test the validity and reliability of the 30 samples to determine whether the questions in the questionnaire can answer the problem daari research. Researchers use traditional Spearman correlation analysis because the data collected in the form ordinal data. The hypothesis of this study is the researchers expect the relationship between Trans Metro bus is cheaper with frequent public use Trans Metro bus as public transport. The survey results revealed that indeed tetdapat relationship between Trans Metro bus fare by frequent public use of public transport as a means of transportation. This research also demonstrated Trans Metro bus users consists of various backgrounds, not just the lower classes only.Keywords: Correlation, Electoral Decree, reliability, Public Transportation, Validity